2009
DOI: 10.1074/jbc.m109.010033
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Short Hairpin RNA Screening of Jurkat T-cells for Human Proteins Contributing to Productive HIV-1 Replication

Abstract: Short interfering RNAs (siRNAs) have been used to inhibit HIV-1 replication. The durable inhibition of HIV-1 replication by RNA interference has been impeded, however, by a high mutation rate when viral sequences are targeted and by cytotoxicity when cellular genes are knocked down. To identify cellular proteins that contribute to HIV-1 replication that can be chronically silenced without significant cytotoxicity, we employed a shRNA library that targets 54,509 human transcripts. We used this library to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
262
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(270 citation statements)
references
References 36 publications
(53 reference statements)
8
262
0
Order By: Relevance
“…Thus, the chance that resistance mutations are selected in host mRNAs is negligible compared to HIV-1 target sequences. Recent screens revealed several cofactor-encoding mRNAs whose knock-down resulted in diminished HIV-1 replication [63][64][65][66][67] . However, knockdown of cellular proteins at the mRNA level might have negative effects on cell viability and anti-host shRNAs must be carefully designed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the chance that resistance mutations are selected in host mRNAs is negligible compared to HIV-1 target sequences. Recent screens revealed several cofactor-encoding mRNAs whose knock-down resulted in diminished HIV-1 replication [63][64][65][66][67] . However, knockdown of cellular proteins at the mRNA level might have negative effects on cell viability and anti-host shRNAs must be carefully designed.…”
Section: Resultsmentioning
confidence: 99%
“…First, we analyzed the targets of HIV, a member of the lentivirus family that causes AIDS. Putative human genes, identified to have an effect on HIV-1 replication from large-scale functional genomic screens (data compiled from four RNAi datasets) (21)(22)(23)(24) tend to be indispensable nodes ( Fig. 2C, RNAi; and Fig.…”
Section: Understanding Healthy To Disease State Transition Using Networkmentioning
confidence: 99%
“…Both biochemical studies and genome-wide short hairpin/siRNA screens have identified nucleoporins (Nups) as HIV-1 dependency factors that assist nuclear import of the preintegration complex (PIC; Ebina et al, 2004;Goff, 2008;König et al, 2008;Kok et al, 2009;Woodward et al, 2009;Yeung et al, 2009). Nups are also required for the nuclear export of viral factors during the late stages of HIV-1 replication (Zolotukhin and Felber, 1999;Hofmann et al, 2001;Le Rouzic et al, 2002;Kiss et al, 2003;Hutten and Kehlenbach, 2006;Hutten et al, 2009).…”
Section: Introductionmentioning
confidence: 99%